A New Functional Wheat Flour Flatbread (Bazlama) Enriched with High-β-Glucan Hull-Less Barley Flour - Koksel, Hamit; Tekin-Cakmak, Zeynep Hazal; Oruc, Sena; Kilic, Gozde; Ozkan, Kubra; Cetiner, Buket; Sagdic, Osman; Sestili, Francesco; Jilal, Abderrazek (MDPI, 2024)
Although the Med-Diet is a healthy diet model, it is affected by current dietary habits. Therefore, new foods with improved nutritional value should be developed to respond to the needs of people following the Med-Diet. This study was focused on developing high-beta-glucan flat bread (bazlama) with a relatively lower GI. A bread wheat (cv. Tosunbey) flour was enriched with the flour of a high-beta-glucan-content hull-less barley (cv. Chifaa) flour (15, 30, 45 and 60%) to develop a functional bazlama. The nutritional and technological properties of bazlama samples enriched with barley flour were compared with the ones produced from bread wheat. All of the barley flour-enriched bazlama samples had higher yellowness values (b*) than the control (both crumb and crust), which is generally preferred by the consumers. Texture results indicated that bazlama samples became harder with the increase in barley flour supplementation level. The results showed that 3 g of beta-glucan can be provided from the barley flour-enriched bazlama samples (at 45 and 60% levels), and this is the limit to carry health claims. The bazlama samples enriched with barley flour were richer in Mg, K, Mn, Fe, and Zn minerals than the control (100% Tosunbey flour). While the glycemic index (GI) of commercial bread wheat and Tosunbey bazlama samples were high (88.60% and 79.20%, respectively), GI values of the bazlama samples enriched with 60% (64.73) and 45% barley flour (68.65) were medium. The lower GI values of barley flour-enriched bazlama samples are probably due to the higher beta-glucan contents of the bazlama samples. Additionally, as the barley flour supplementation level of the bazlama samples increased, the phenolics and antioxidant capacities of free and bound extracts increased compared to bread wheat bazlama. The results indicated that hull-less barley (cv. Chifaa) with high beta-glucan content may be utilized at relatively higher levels (45 and 60%) to produce bazlama with improved nutritional properties.
Keywords: barley flour; bazlama; antioxidant capacity; glycemic index; mineral compositions; ANTIOXIDANT ACTIVITY; BREAD; QUALITY; Food Science & Technology